Effect of Ketorolac on Pain Scores and Length of Stay in Post Anaesthetic Care Unit after Major Abdominal Surgery - Amanat Khan, Amanat Khan; Ghulam Sabir Iqbal, Ghulam Sabir Iqbal; Azra Naseem, Azra Naseem; Mohammad Usman Ahmed, Mohammad Usman Ahmed; Omer Salahuddin, Omer Salahuddin (Journal of Rawalpindi Medical College, 2007)
Background: To find out the effectiveness of ketorolac administered at the end of surgery in reducing pain scores and the length of stay in the Post Anaesthetic Care Unit (PACU) for the patients undergoing major abdominal surgery. Methods: This interventional study, a double blind randomized control trial was conducted at POF Hospital, Wah Cantt, over a three year period starting 2004. One hundred adult patients, planned for major surgery fulfilling the inclusion criteria were randomized by simple random numbers table into two groups by codes. At the end of procedure, 30mg ketorolac (an NSAID) was given intravenously to every member of ketorolac group and 10 ml normal saline I/V (placebo) was given to every member in control group. All the patients were shifted to PACU. The doctor in charge PACU had to decide the length of stay based on two parameters; 1) Pain score on the basis of visual analogue score (VAS) and 2) Salim ABC score for recovery room stay. Results: The initial mean post operative scores in the PACU were lower for ketorolac group, 3.6 on Visual analogue score(VAS) with a standard deviation (S.D.) of +/-0.9, and for control group the respective mean postoperative pain score was 5.4 with the S.D. of +/-1.3. This difference was of statistical significance with a p value of less than 0.05. The mean length of stay in PACU for ketorolac group was 97 minutes with an S.D. of +/-30 minutes, while the corresponding mean and S.D. for the control group were 134 minutes and +/-35 minutes respectively which also depicted a difference of statistical significance with a p value of less than 0.05. Conclusion: Ketorolac administered I/V at the end of surgery effectively controls the immediate post operative pain and reduces the length of stay in PACU.